Acute attenuation of fatigue after sodium bicarbonate supplementation does not manifest into greater training adaptations after 10-weeks of resistance training exercise - Siegler, J. C.; Marshall, P. W. M.; Finn, H.; Cross, R.; Mudie, K. (PLOS ONE, 2018)
In two concurrent studies, we aimed to a) confirm the acute effect of 0.3 g·kg-1 body weight (BW) sodium bicarbonate (NaHCO3) supplementation on central and peripheral mechanisms associated with explosive power (Study 1) and b) determine whether chronic NaHCO3 supplementation would improve the adaptive response of the neuromuscular system during a 10-week resistance training program (Study 2). Methods: Eight resistance trained participants volunteered after providing written consent. The experimental design consisted of a week of baseline testing, followed by ten weeks of training with progress measures performed in Week 5. Study 1 involved neuromuscular measurements before and after the leg extension portion of a power based training session performed in Week 1. Changes in maximal torque (MVT) and rates of torque development (RTD), along with other variables derived from femoral nerve stimulation (e.g. voluntary activation, neural recruitment) were analysed to determine the extent of fatigue under NaHCO3 or placebo conditions. Changes in these same variables, coupled with functional 1-repetition maximum leg extension strength, were measured in Study 2 from baseline (Week 0) to Week 5, and again at Week 10. Results and conclusion: In Study 1, we observed a decline after the leg extension task in both MVT (~ 30%) and rates of torque production (RTD) irrespective of acid-base status, however the decline in maximal RTD (RTDMAX) was nearly 20% less in the NaHCO3 condition when compared to placebo (mean difference of 294.8 ± 133.4 Nm·s-1 (95% CI -583.1 to -6.5 Nm, p < 0.05)). The primary finding in Study 2, however, suggests that introducing NaHCO3 repeatedly during a 10-week RT program does not confer any additional benefit to the mechanisms (and subsequent adaptive processes) related to explosive power production.